How Do Macroeconomic and Bank‐specific Variables Influence Profitability in the Austrian Banking Sector? Evidence from a Panel Vector Autoregression Analysis. (21st June 2017) - Sigmund, Michael; Gunter, Ulrich; Krenn, Gerald
Abstract : We examine the determinants of the net interest margin (NIM) and the net fee and commission income ratio (NFCIR) of Austrian banks as well as their interrelationship and whether portfolio separation between loan and deposit categories holds. We describe a conceptual framework for the profit optimization problem faced by banks as a Bertrand game with differentiated products and intrafirm product interactions. We contribute to the literature by factoring in banks' business models in terms of their balance sheet structure. We empirically assess the implications of our conceptual framework using a unique supervisory data set of around 48, 000 observations between 1998 and 2014. We estimate two panel vector autoregression models with a novel panel vector autoregression code. Apart from quantifying the contributions of the determinants (e.g., risk weighted assets, leverage ratio, loan loss provision ratio) to NIM and NFCIR, the empirical results show that interest income and fee and commission income should be regarded as strategic complements within a bank. We further conclude that portfolio separation between different loan and deposit categories does not hold.